Use of mobile phones by male and female Greek students. (6th August 2008) - Economides, Anastasios A.; Grousopoulou, Amalia
Mobile technology is a continuously growing domain, and research activities regarding its use are quite intensive. A questionnaire regarding the use of mobile devices was developed and distributed to 416 students in a Greek University. There were completed 384 questionnaires. The results revealed that students use their mobiles mostly for phone calls and Short Message Service (SMS). They also tend to use their mobiles to take photos and activate the reminder. However, they do not deal with many of the devices' operations. They use their mobiles to communicate (telephone, SMS and e-mail) mostly with their boy/girlfriend, then with their friends. They use their mobiles mostly at home, then at the university. Also, they consider health issues as the main reason to limit the use of their mobiles. Finally, there was not a statistically significant relationship between genders and their preferences.